OBJECTIVES, TASKS AND FUNCTIONS OF THE EXPERTISE OF NORMATIVE LEGAL ACTS - N. S. Titov (Russian Journal of Economics and Law)
Objective: to identify goals, objectives and functions of the expertise of normative legal acts (NLA) and to disclose their contents through the essence of law, which will improve the quality of the expertise.Methods: dialectical, formal-dogmatic, comparative, functional analysis, synthesis.Results: the definition is proposed of the purpose of the normative legal acts expertise as assurance of the law quality, the achievement of which is impossible without performing tasks defined in the article. Accordingly, the two functions of the NLA expertise are determined, which are aimed at identifying of what is the inverse of the quality of law: the legal-technical and social functions. The legal-technical function is aimed at solving the task of establishing formal certainty, clarity, unambiguousness and consistency of the rule of law, namely the rights, duties and prohibitions, conditions of their emergence, change and termination, as well as measures of state protection. The social function is aimed at solving the task of identifying social benefits of participants of the regulated relations, established in the regulatory acts.Scientific novelty: the content of goals, objectives and functions of the expertise of normative legal acts is revealed through the essence of law, which, from the formal-legal side consists in ordering social relations with formally-defined rules of behavior, and from the social side - in finding out in favour of whom the social relations are regulated.Practical significance: accurate determination of the NLA research directions will provide continuity and consistency of NLA expertise and verifiability of the results.